Pelembagaan Pendidikan Islam Menurut Agussani - rahmadmulyadi (Institut Agama Islam Negeri (IAIN) Metro, 2024)
The institutionalization of Islamic education, both in the form of Islamic education subjects and madrasa institutions, still receives discriminatory treatment. This shows that there is inequality in the treatment of Islamic education compared to general education. So in this case the aim of writing this research is to find out the views of the institutionalization of Islamic education, its implementation, as well as the prospects and challenges in carrying out the institutionalization of Islamic education according to Agussani. The method used in this research is the library research method (Library Study) with a semiotic approach. The results of this research show that the institutionalization of Islamic education in Indonesia, according to Agussani, still receives discriminatory treatment from general education, so there is a need to implement good institutionalization of Islamic education. By overcoming these challenges and making good use of its prospects, Islamic education can continue to develop and make a significant contribution in shaping the future of a generation of Muslims who are competent, have integrity and are globally competitive. In conclusion from the views, implementation as well as the prospects and challenges faced, the successful implementation of the institutionalization of Islamic education requires a strong commitment from all stakeholders, including institutional leaders, teachers, students, parents and the community.